Reviewing the Book "Gender in Ethics Opinion since the 3rd Century BH to the 4th Century SH" - Nayereh Dalir (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study aims at reviewing and criticizing the Book "Gender in Ethics Opinion Since the 3rd Century BH to the 4th Century SH", which encompasses a period of 7 centuries in two important periods of Iranian history, i.e. the ancient period and the early centuries of the Islamic period. The author intends to explain the opinions, views, legal and jurisprudential issues found in this time period on female gender in the literature of this period as specific ethical opinions and their effects. Thus, he discusses two important points in Iranian history, the turning point of which is the end of the ancient period and the arrival of Islam by providing a broad definition of ethical ideas. It is the findings of the present study regarding the criticism and review of this work, while being problem-centered and raising many questions as its advantage, that deal with some aspects of form and structure criticism, methodological, content, and literary criticism.